2013
DOI: 10.4049/jimmunol.1103812
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Inhibits Surface Expression of Complement Receptor 1 in Monocytes/Macrophages, Causing Decreased Immune Complex Internalization

Abstract: Complement receptor 1 (CR1) expressed on the surface of phagocytic cells binds complement-bound IC playing an important role in the clearance of circulating immunecomplexes (IC). This receptor is critical to prevent accumulation of IC, which can contribute to inflammatory pathology. Accumulation of circulating IC is frequently observed during malaria, although the factors contributing to this accumulation are not clearly understood. We have observed that the surface expression of CR1 on monocyte/macrophages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 45 publications
2
23
2
Order By: Relevance
“…Lower CR1 expression has been associated with improper IC clearance in mice models. 24 Furthermore, CR1 expression was found to be inversely correlated with IC deposition in the kidney 24 increasing the possibility of renal damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lower CR1 expression has been associated with improper IC clearance in mice models. 24 Furthermore, CR1 expression was found to be inversely correlated with IC deposition in the kidney 24 increasing the possibility of renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent case-control study and meta-analysis, we showed that the CR1 minor alleles associated with lower levels of expression of CR1 are associated with protection against severe Plasmodium falciparum malaria, and they are highly prevalent in malaria endemic areas 18. In a murine model, Plasmodium yoelli infection decreased CR1 expression on monocytes and hindered IC internalisation which recovered after the clearance of parasites 24. Furthermore, human subjects infected with P. falciparum or P. vivax also display lower CR1 expression on monocytes compared with uninfected individuals 24.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Circulating ICs can interact with CD16/Fcγ RIII resulting in phagocyte activation and augmentation of the inflammatory response. Both in patients and in mice with malaria, CR1 surface expression is reduced on monocytes, macrophages and B cells (but not on PMNs) resulting in increased levels of circulating ICs (Fernandez-Arias et al 2013). Furthermore, by the presence of CR1 on the surface of human RBCs, RBCs participate in IC clearance by transferring CR1-bound ICs to phagocytic cells (Fernandez-Arias et al 2013).…”
Section: Activation Of the Complement Systemmentioning
confidence: 99%